Contemporary Forms of Female Islamic Leadership, Activism, and Interpretation in Morocco. (13th November 2018) - Gray, Doris
Abstract : Female Islamic leadership in Morocco is marked by male patronage and fragmentation. Women in leadership positions—in the religious, political or economic realm—rise and remain dependent on male power. This article focuses on the religious/political arena where leading women do not pursue a common goal, but have varying understandings of gender justice or equality. Various developments in Morocco point to the creation of a middle ground for female activism between Western secularism and Islamism. Such developments can easily be overlooked when more radical voices gain the spotlight and generate media controversy.